Efektivitas Latihan Plyometric terhadap Peningkatan Lompatan Vertikal pada Pemain Voli - Ahmad Syabaruddin; Fery Brian Banjarnahor; Deni Rahman Marpaung (Jurnal Pengabdian Masyarakat Waradin, 2025)
This study aims to analyze the effectiveness of plyometric training in improving vertical jumping ability in volleyball players. This research uses a literature study method by collecting and analyzing data from various relevant literature. The results showed that plyometric exercises, such as rim jumps, single jumps, hurdle hopping, and box jumps, significantly increased the explosive power and muscle strength required for vertical jumps. Factors that influence the effectiveness of this exercise include intensity, duration, and technique used. In addition, the combination of plyometric training and weight training has been shown to improve neuromuscular ability, muscle strength, and speed, which are very important in explosive movements such as blocks and smashes in volleyball. This study concludes that the integration of plyometric training in volleyball athletes’ training programs is highly recommended to improve vertical jump performance and reduce the risk of injury.